Behavioural factors of willingness to save long term – a factor analysis - Olechnowicz-Szewczyk, Agata; Babula, Elżbieta (Behawioralne aspekty skłonności do oszczędzania długoterminowego – analiza czynnikowa, 2021)
The study conducted an exploratory factor analysis of the Willingness to Save Long Term Scale (WSL). It developed a set of 30 appropriate and homogeneous items on behavioural aspects of willingness to save long term. It also determined the reliability indices of the scale and established its factor structure. The study population comprised 232 students from the Faculty of Economics at the University of Gdańsk. The outcome was subjected to Exploratory Factor Analysis (EFA) with oblimin rotation. The results of the EFA revealed that, with KMO > 0.8, the data were sufficient to undergo a factor analysis, while Bartlett’s test (p < 0.001) revealed a satisfactory EFA. The reliability coefficient Cronbach’s α was statistically significant (0.719), indicating a high degree of internal consistency. The study concluded that the WSL Scale instrument was valid and reliable for measuring the phenomenon of willingness to save long term from the behavioural perspective. The five factors revealed by the EFA could be used as a guide to better understand how the decision-making process to save for retirement works
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 2, s. 102-113